Soldering Characteristics And Corrosion Behaviour Of Indium Added To SAC305 Solder Alloy - Amiruddin, Atikah Zulaikha (Universiti Sains Malaysia, 2018)
Alloying element indium is chosen in order to study the effects of indium tocorrosion resistance of Sn-Ag-Cu solder alloy. In this project, the composition of indium was varied ranging from 1-4 wt. % and were added into Sn–3.0Ag-0.5Cu solder. The effects of indium addition on melting property, microstructure, corrosion resistance, wettability of the solder alloys were studied. For thermal properties, it can be determined that more addition of indium lowered the melting point of SAC305 solder alloy as the melting temperature is reduced from 229.55 ○C to 219.91 ○C. For morphological analysis of bulk sample of solder alloy, it can be determined that 1 wt. % of In addition to the solder alloy composition is already adequate as fine grain and uniformly distributed microstructure can be obtained. Fine grain size acquired due to 1 wt. % of In addition to solder alloy lead to greater spreading area with 6.18 mm and lower wetting angle with 14.59○ which resulted in good wettability of solder alloy. In addition, based on the data acquired from plotted polarization curve corrosion rate analysis, it can be determined that the addition of 1 wt.% of In gives the lowest corrosion rate and high corrosion resistance compared to other prepared of solder alloys. Thus, it can be concluded that a mere amount of 1 wt. % of In addition to the solder alloy composition is already adequate in order to achieve desired properties like fine grain and uniformly distributed microstructure, good wettability, low thermal properties and good corrosion for SAC305 solder alloy.